Study of vitamin D levels in pediatric patients on antiepileptic monotherapy - Salam, Fahim; Mohammad, Shabir; Singhal, Nehal; Verma, Suresh Kumar; Verma, Ayush (International Journal of Contemporary Pediatrics, 2026)
Background: Epilepsy affects nearly 50 million people worldwide, with childhood onset common. Long-term antiepileptic drug (AED) therapy, including valproate (VPA), carbamazepine (CBZ), and levetiracetam (LEV), may adversely influence vitamin D metabolism, impacting bone and neurological health. With limited pediatric data and no supplementation guidelines, this study investigates the association between AED monotherapy, vitamin D status, and biochemical outcomes in children. The aim of this study is to evaluate if CBZ, VPA and LEV as monotherapy is associated with vitamin D deficiency among children with epilepsy. Results: In 86 pediatric patients (52.3% female), VPA (43%) and CBZ (24.4%) significantly reduced Vitamin D3 to 22.7 ng/ml and calcium to 9.1 mg/dl at 6 months, while elevating ALP to 281.4 IU/L and 267.7 IU/L, respectively. LEV (32.6%) showed milder effects (28.7 ng/ml, 202.5 IU/L). Methods: After ethics approval, children aged 5-18 years with epilepsy at Umaid/MDM Hospital were screened. Baseline serum vitamin D3, calcium, phosphate, and ALP were measured using chemiluminescence. Patients with normal vitamin D3 (>20 ng/ml) were enrolled and initiated on VPA, LEV, or CBZ, with follow-up monitoring for biochemical changes. Statistical tool used is SPSS v.22. Conclusions: VPA and CBZ were associated with significant declines in vitamin D and calcium levels, along with elevated ALP, indicating adverse effects on bone health in pediatric epilepsy patients. LEV showed comparatively milder effects. Routine monitoring and proactive management of bone health are crucial for all children on long-term AED therapy.